Cryptops (Cryptops) spelaeoraptor n. sp. a remarkable troglobitic species (Chilopoda: Scolopendromorpha) from Brazil - Ázara, Ludson Neves De; Ferreira, Rodrigo Lopes (Zootaxa, 2014)
Cryptops (Cryptops) spelaeoraptor is here described from Toca do Gonçalo cave, Bahia state, Brazil. This species presents highly troglomorphic traits and can be separated from all other species of Cryptops by possessing a unique trait in Scolopendromorpha: the ultimate pair of legs presents saw teeth on each of the prefemur to tarsus 2 (rather than being concentrated on the tibia and tarsus 1) numbering 28+30+14+17+17.